2001
DOI: 10.1093/geronb/56.1.p12
|View full text |Cite
|
Sign up to set email alerts
|

The Disablement Process in Very Late Life: A Study of the Oldest-Old in Sweden

Abstract: The study examines physical and functional health problems and their relationship to the activity of daily living (ADL) disability experience of a cross-section of Swedish men and women aged over 80 years (N = 203). Using a model of disablement, the relationships among disability variables were simultaneously explored. Results confirmed relatively high rates of disability in this age group, with 36% of respondents having some basic ADL difficulty. Functional impairments (vision and grip strength) and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 50 publications
8
118
0
3
Order By: Relevance
“…A tendency toward depression has been reported to have an adverse influence on the ADL in some previous studies (Rantanen et al 2000;Femia et al 2001;Wada et al 2004). The influence has been explained by a behavioral scientific and biological mechanism as follows: Depressed mood induces decreased appetite, weight loss, and decreased activity, resulting in the decline of muscle strength (Rantanen et al 2000).…”
Section: Discussionmentioning
confidence: 91%
“…A tendency toward depression has been reported to have an adverse influence on the ADL in some previous studies (Rantanen et al 2000;Femia et al 2001;Wada et al 2004). The influence has been explained by a behavioral scientific and biological mechanism as follows: Depressed mood induces decreased appetite, weight loss, and decreased activity, resulting in the decline of muscle strength (Rantanen et al 2000).…”
Section: Discussionmentioning
confidence: 91%
“…Entre eles, está uma investigação (9) realizada com 203 idosos longevos suecos, a qual objetivou identificar os problemas de saúde físicos e funcionais dos idosos e sua relação entre as atividades de vida diária. Como resultado, o estudo demonstrou que 36% desses idosos longevos possuíam dificuldade na realização de pelo menos uma das atividades de vida diária (9) .…”
Section: Introductionunclassified
“…Entre eles, está uma investigação (9) realizada com 203 idosos longevos suecos, a qual objetivou identificar os problemas de saúde físicos e funcionais dos idosos e sua relação entre as atividades de vida diária. Como resultado, o estudo demonstrou que 36% desses idosos longevos possuíam dificuldade na realização de pelo menos uma das atividades de vida diária (9) . Outro estudo (10) , realizado com 8.805 idosos chineses na faixa etária entre 80 e 105 anos, observou que os idosos oriundos da zona rural possuem níveis de atividade de vida diária maiores do que aqueles residentes na zona urbana, podendo ser considerados idosos mais ativos.…”
Section: Introductionunclassified
“…There have, however, been partial tests published in three noteworthy studies (Femia et al 2001;Lawrence and Jette 1996;Peek et al 2003). Using longitudinal analyses, Lawrence and Jette's (1996) study supported the causal directionality of the relationships between impairments, functional limitations, and disability.…”
Section: Introductionmentioning
confidence: 83%
“…Using longitudinal analyses, Lawrence and Jette's (1996) study supported the causal directionality of the relationships between impairments, functional limitations, and disability. Femia et al (2001) and Peek et al (2003) found evidence for mediation between variables within the main pathway, as well as evidence that the main pathway variables have indirect effects on disability through various psychosocial factors (depression, subjective health, and social integration in Femia's study, and perceived support in Peek's study). In fact, Femia concluded that the results ''suggest disability to be as much a function of an individual's psychosocial characteristics as the degree of functional limitations and functional impairments '' (2001, p. 20).…”
Section: Introductionmentioning
confidence: 95%